Effect of continuous negative pressure water supply on the growth, development and physiological mechanism of Capsicum annuum L. - Di LI; Huai-yu LONG; Shu-xiang ZHANG; Xue-ping WU; Hong-ying SHAO; Peng WANG (Journal of Integrative Agriculture)
Effects of continuous negative pressure water supply on water consumption, growth and development, as well as physiological mechanism and quality of Capsicum annuum L. were investigated in this paper. Meanwhile, the optimal negative pressure water supply conditions for growth of C. annuum L. were screened out to achieve the goals of water conservation, high yield and high quality, thus providing theoretical foundation for its field production. The pot experiment within the greenhouse was utilized; the continuous negative pressure water supply was adopted; the four treatments, artificial watering (CK), –5 kPa (T1), –10 kPa (T2), and –15 kPa (T3) were set; and the daily water consumption, yield, as well as the biomass, nitrate reductase, root activity, vitamin C, capsaicin, and nutrient uptakes of nitrogen (N), phosphorus (P) and potassium (K) during various stages of its growth were determined. Compared with CK, when the water supply pressure was controlled at –5 to –15 kPa in the experiment, the total water consumption of C. annuum L. reduced by 53.42 to 67.75%, the total water consumption intensity reduced by 54.29 to 67.14%, and the water use efficiency increased by 12.66 to 124.67%. The N accumulation in a single strain of C. annuum L. from the color turning stage to the red ripe stage increased by 15.99 to 100.55%, respectively, compared with that of CK; the P accumulation increased by 20.47 to 154.00% relative to that of CK, and the K accumulation increased by 64.92 to 144.9% compared with that of CK. Compared with CK, C. annuum L. yield was remarkably improved by 13.79% at T1, and contents of vitamin C, capsaicin as well as carotenoids at all growth stages were enhanced by 13.42–147.01%, 11.54–71.01%, and 41.1–568.06%, respectively. Nitrate reductase activity, root activity and chlorophyll (a+b) were markedly increased by 335.78–500%, 79.6–140.68% and 114.95–676.19%, respectively, from immature stage to full ripe stage. Adopting the continuous negative pressure water supply for C. annuum L. has a significant water-saving effect, and the water supply pressure being stable at –5 kPa contributes to its growth and development, improves yield, enhances root activity, promotes nutrient uptake, and improves its quality, thus achieving the effects of water conservation, high yield, high quality and high efficiency.